2015
DOI: 10.1124/mol.114.096495
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor–Interacting Protein 1a Modulates CB1 Receptor Signaling and Regulation

Abstract: Cannabinoid CB 1 receptors (CB 1 Rs) mediate the presynaptic effects of endocannabinoids in the central nervous system (CNS) and most behavioral effects of exogenous cannabinoids. Cannabinoid receptor-interacting protein 1a (CRIP 1a ) binds to the CB 1 R C-terminus and can attenuate constitutive CB 1 R-mediated inhibition of Ca 21 channel activity. We now demonstrate cellular colocalization of CRIP 1a at neuronal elements in the CNS and show that CRIP 1a inhibits both constitutive and agonist-stimulated CB 1 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 64 publications
(79 reference statements)
3
49
0
1
Order By: Relevance
“…CRIP1a overexpression decreased CB 1 Rstimulated [ 35 S]GTPgS binding to Gi3 (Blume et al, 2015), an interaction believed to involve the C-terminus of the CB 1 R (Mukhopadhyay et al, 2000;Mukhopadhyay and Howlett, 2001). Moreover, we found that CRIP1a overexpression in CB 1 R-expressing HEK293 cells inhibited CB 1 R downregulation in response to prolonged agonist occupancy (Smith et al, 2015), whereas genetic deletion of b-arrestin 2 inhibited CB 1 R downregulation in mice (Nguyen et al, 2012). These findings led us to hypothesize that CRIP1a could also influence the interaction of the CB 1 R with b-arrestins, known to function in internalization via the CB 1 R C-terminus (Hsieh et al, 1999;Daigle et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…CRIP1a overexpression decreased CB 1 Rstimulated [ 35 S]GTPgS binding to Gi3 (Blume et al, 2015), an interaction believed to involve the C-terminus of the CB 1 R (Mukhopadhyay et al, 2000;Mukhopadhyay and Howlett, 2001). Moreover, we found that CRIP1a overexpression in CB 1 R-expressing HEK293 cells inhibited CB 1 R downregulation in response to prolonged agonist occupancy (Smith et al, 2015), whereas genetic deletion of b-arrestin 2 inhibited CB 1 R downregulation in mice (Nguyen et al, 2012). These findings led us to hypothesize that CRIP1a could also influence the interaction of the CB 1 R with b-arrestins, known to function in internalization via the CB 1 R C-terminus (Hsieh et al, 1999;Daigle et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…Cell Culture and Immunocytochemistry Determination of CB 1 R Internalization. We previously reported the development and characterization of stable CRIP1a overexpression (XS-1 and XS-5) and siRNA-knockdown (KD-2C and KD-2F) N18TG2 neuroblastoma clones (passage numbers 30-38) (Blume et al, 2015;Smith et al, 2015). Wild-type, empty-vector control, and transgenic clones were maintained at 37°C under a 5% CO 2 atmosphere in Dulbecco's modified Eagle's medium:Ham's F12 (1:1) complete with GlutaMax, sodium bicarbonate, and pyridoxine-HCl, supplemented with penicillin (100 units/ml) and streptomycin (100 mg/ml) (Gibco Life Technologies, Gaithersburg, MD) and 10% heat-inactivated bovine serum (Gemini Bioproducts, West Sacramento, CA).…”
Section: Materials the National Institute Of Drug Abuse Drug Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous CRIP1a reversed CB 1 receptor-mediated tonic inhibition of Ca 2+ currents, whereas CRIP1b could not[11]. CRIP1a-knockdown clones in the model neuroblastoma N18TG2 cells exhibited enhanced ERK1/2 phosphorylation efficacy in response to CP55940 and displayed a leftward shift in CP55940-mediated inhibition of forskolin-stimulated cAMP accumulation [12,13]. CB 1 receptor-mediated G i3 and G o activation by CP55940 was attenuated by CRIP1a over-expression, but robustly enhanced in CRIP1a-knockdown clones.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, CP55940-mediated G i1 and G i2 activation was significant enhanced in cells over-expressing CRIP1a, but not inCRIP1a-knockdown clones [14]. These studies suggest that endogenous levels of CRIP1a modulate CB 1 receptor-mediated signal transduction by facilitating a G i/o subtype preference for G i1 and G i2 , accompanied by an overall suppression of G protein-mediated signaling in neuronal cells [12,13]. …”
Section: Introductionmentioning
confidence: 99%